The problem of maintenance management in government building / Muhamad Raqib Shaari - Shaari, Muhamad Raqib (Faculty of Architecture, Planning and Surveying, 2009)
This study was aimed to study about the effectiveness of roof covering in UiTM Shah Alam. Recently, there are several cases that present situation of roofing problems in government building.The study is based on roof covering material and maintenance programmed for roof and also will focus on the problems that occur on the building. In this dissertation, the main objectives is to identify construction method related to roof covering material and study the problems that occurs in roof covering material. The area of the study is in UiTM Shah Alam campus. So, this study will analyze the effectiveness of each types of the roof covering material in the campus. Finally, the choosing of the case studies will explain for more detail in chapter 4.